Constructing a Novel E-Learning Course, Educational Computational Chemistry through Instructional Design Approach in the TPASK Framework - José Hernández-Ramos; Jorge Rodríguez-Becerra; Lizethly Cáceres-Jensen; Maija Aksela (MDPI AG, 2023)
The educational scenario after the COVID-19 confinement presents new challenges for teachers. Technological advances require teachers to be prepared for instruction through technology, and with this, the need for e-learning courses arose to strengthen this knowledge. This article aims to describe an innovative e-learning course in Educational Computational Chemistry (ECC) for in-service chemistry teachers through an Instructional Design (ID) that allows the development of the constructs associated with the Technological Pedagogical Science Knowledge (TPASK) framework. From the literature overview, relevant findings were raised concerning ID and its potential technological support. The results indicate that an effective ID must present general elements, such as the organisation and generation of content, progress monitoring, and feedback instances. However, the stages of engagement, flexibility, and positioning are relevant elements. These design elements are linked to emerging technological tools, such as artificial intelligence for generating audiovisual material, interactive content development, and event logs. In addition, positive results are evident from the teachers who participated in the ECC e-learning course, who project the knowledge, computer skills, and learning acquired into their professional work as chemistry teachers. Based on the above, a course design for ECC is proposed with general guidelines that contribute to the continuous training of in-service chemistry teachers.